Polycyclic aromatic hydrocarbons in street dust of Marvdasht city, SW Iran: concentration, health risk assessment and source apportionment. (28th June 2019) - Moore, Farid; Birami, Farideh Amini; Keshavarzi, Behnam; Shahidi, Ommolbanin
The status, health risk and sources of street-dust-borne polycyclic aromatic hydrocarbons (PAHs) were investigated in Marvdasht city. The total concentration of 15 PAHs ranged from 932.85 to 5030 μg kg -1 with a mean of 2185.7 μg kg -1 . The PAHs contained 2-6 rings and the level of five carcinogenic PAHs generally accounted for 5-40% of total concentration. The statistical analysis and diagnostic ratios demonstrated that the main emission source of PAHs is traffic. The toxic equivalent concentrations (TEQs) of PAHs in street dust ranged from 12.91 to 1160.88 μg kg -1, with a mean of 257.18 μg kg -1 . High correlation coefficients (r > 0.9, p < 0.01) between benzo[a]pyrene, dibenzo[a, h]anthracene, benzo[g, h, i]perylene, indene and toxicity equivalent concentrations of street dust indicated that these PAHs are predominant contributors to TEQ. The results of total incremental lifetime cancer risk (ILCR) demonstrated that Marvdasht's residents are potentially exposed to high cancer risk via dust ingestion and dermal contact.